PENGARUH PRESTASI KERJA DAN LOYALITAS KARYAWAN TERHADAP PROMOSI JABATAN PADA PT.DJITOE INDONESIAN TOBACCO KOTA SURAKARTA - Zaenab Paska Triani; Cicilia Dyah Sulistyaningrum I.; Susantiningrum - - (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2019)
The research is aimed to identify whetever or not: (1) there’s positive and significant effect of work performance to be job promotion; (2 )there’s positive and significant effect of employees loyalty to be job promotion; (3) there’s positive and significant effect between work performance and employee loyalty together toward job promotion. This study used quantitative approach. The population of this research was 229 people and the total sample of this study were 70 people taken by proportional random sampling. The method of collecting data this research was used observation, questionnaires, and analysis document. The technique of analizying the data used multiple regression analysis by using SPSS version 20. The results of this research showed that:(1) there was positive and significant influence between the variables of work performance to job promotion (tcount=3.503, sign<0,05), (2 )there was positive and significant influence between employees loyalty to job promotion (tcount=3.785, sign<0,05), (3) there was positive and significant influence between work performance and employee loyalty together toward job promotion (Fcount=17.172, sign<0,05). The multiple linear regression equation is Ŷ = 16,881 + 0,475 X1 + 0,490 X2.